2020
DOI: 10.1021/acsaem.0c01239
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Bubble Detachment in Porous Transport Layers with Patterned Through-Pores

Abstract: Mass transport losses ultimately suppress gas evolving electrochemical energy conversion technologies, such as fuel cells and carbon dioxide electrolyzers, from reaching the high current densities needed to realize commercial success. In this work, we reach ultrahigh current densities up to 9 A/cm 2 in a polymer electrolyte membrane (PEM) water electrolyzer with the application of custom porous transport layers (PTLs) with patterned through-pores (PTPs), and we reduce the mass transport overpotentials of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 61 publications
1
47
0
Order By: Relevance
“…Connected channels are mainly responsible for the nonwetting flow and the rim of the pores is involved in the wetting-phase exchange. The big pores might accelerate the gas transport and less gas accumulates near the catalyst layer MPL interface, similar to the modification of commercial PTLs reported by Lee et al, 74 thus, the water transport also is improved. Another explanation for the improved performance is that the favored nucleation sites are outside of the NiMPL-PTL due to a diffusion flux without nucleation inside the small pores.…”
Section: Numerical Simulationssupporting
confidence: 70%
“…Connected channels are mainly responsible for the nonwetting flow and the rim of the pores is involved in the wetting-phase exchange. The big pores might accelerate the gas transport and less gas accumulates near the catalyst layer MPL interface, similar to the modification of commercial PTLs reported by Lee et al, 74 thus, the water transport also is improved. Another explanation for the improved performance is that the favored nucleation sites are outside of the NiMPL-PTL due to a diffusion flux without nucleation inside the small pores.…”
Section: Numerical Simulationssupporting
confidence: 70%
“…Similar observations are reported in the previous literature. 46,47 First, Lee et al revealed via modelling and in operando neutron imaging experiments that having a porosity gradient from low to high porosity facilitates mass transport during electrolysis. Moreover, they further 47 demonstrated that when a custom pore structure was applied to the PTL (i.e., pores with diameters excessively larger than the average pores in the PTL), the gas saturation at the catalyst layer-PTL interface was significantly reduced and mass transport behaviour was enhanced particularly at higher current density operation.…”
Section: Papermentioning
confidence: 99%
“…The more hydrophilic surface of IrO 2 /N-TiO 2 indicates superior electrolyte penetration and gas adsorption-desorption. To verify the superior kinetics and mass transport of IrO 2 /N-TiO 2 , the voltage losses of kinetic losses, ohmic losses, and mass transport losses were estimated [19]. For an electrolysis cell, the cell voltage is the sum of thermodynamic voltage E 0 (p, T), ohmic losses (R j), kinetics losses, and mass transport losses (Equation ( 2)).…”
Section: Origin Of the Efficient Electrocatalytic Performancesmentioning
confidence: 99%